Download presentation

Presentation is loading. Please wait.

Published byAndrew Spencer Copeland Modified over 6 years ago

1
3.5 – Solving Systems of Equations in Three Variables

2
Ex. x + 2y + z = 10 2x – y + 3z = - 5 2x – 3y – 5z = 27

3
3.5 – Solving Systems of Equations in Three Variables Ex. x + 2y + z = 10 2x – y + 3z = - 5 2x – 3y – 5z = 27

4
3.5 – Solving Systems of Equations in Three Variables Ex. x + 2y + z = 10 2x – y + 3z = - 5 2x – 3y – 5z = 27 x + 2y + z = 10 2x – y + 3z = - 5

5
3.5 – Solving Systems of Equations in Three Variables Ex. x + 2y + z = 10 2x – y + 3z = - 5 2x – 3y – 5z = 27 x + 2y + z = 10 2[2x – y + 3z = - 5]

6
3.5 – Solving Systems of Equations in Three Variables Ex. x + 2y + z = 10 2x – y + 3z = - 5 2x – 3y – 5z = 27 x + 2y + z = 10 2[2x – y + 3z = - 5] x + 2y + z = 10 4x – 2y + 6z = -10

7
3.5 – Solving Systems of Equations in Three Variables Ex. x + 2y + z = 10 2x – y + 3z = - 5 2x – 3y – 5z = 27 x + 2y + z = 10 2[2x – y + 3z = - 5] x + 2y + z = 10 4x – 2y + 6z = -10 5x + 7z = 0

8
3.5 – Solving Systems of Equations in Three Variables Ex. x + 2y + z = 10 2x – y + 3z = - 5 2x – 3y – 5z = 27 x + 2y + z = 10 2[2x – y + 3z = - 5] x + 2y + z = 10 4x – 2y + 6z = -10 5x + 7z = 0

9
3.5 – Solving Systems of Equations in Three Variables Ex. x + 2y + z = 10 2x – y + 3z = - 5 2x – 3y – 5z = 27 x + 2y + z = 10 2[2x – y + 3z = - 5] x + 2y + z = 10 4x – 2y + 6z = -10 5x + 7z = 0

10
3.5 – Solving Systems of Equations in Three Variables Ex. x + 2y + z = 10 2x – y + 3z = - 5 2x – 3y – 5z = 27 x + 2y + z = 102x – y + 3z = - 5 2[2x – y + 3z = - 5]2x – 3y – 5z = 27 x + 2y + z = 10 4x – 2y + 6z = -10 5x + 7z = 0

11
3.5 – Solving Systems of Equations in Three Variables Ex. x + 2y + z = 10 2x – y + 3z = - 5 2x – 3y – 5z = 27 x + 2y + z = 102x – y + 3z = - 5 2[2x – y + 3z = - 5] 2x – 3y – 5z = 27 x + 2y + z = 10 4x – 2y + 6z = -10 5x + 7z = 0

12
3.5 – Solving Systems of Equations in Three Variables Ex. x + 2y + z = 10 2x – y + 3z = - 5 2x – 3y – 5z = 27 x + 2y + z = 10 -3[2x – y + 3z = - 5] 2[2x – y + 3z = - 5] 2x – 3y – 5z = 27 x + 2y + z = 10 4x – 2y + 6z = -10 5x + 7z = 0

13
3.5 – Solving Systems of Equations in Three Variables Ex. x + 2y + z = 10 2x – y + 3z = - 5 2x – 3y – 5z = 27 x + 2y + z = 10 -3[2x – y + 3z = - 5] 2[2x – y + 3z = - 5] 2x – 3y – 5z = 27 x + 2y + z = 10 -6x + 3y – 9z = 15 4x – 2y + 6z = -10 2x – 3y – 5z = 27 5x + 7z = 0

14
3.5 – Solving Systems of Equations in Three Variables Ex. x + 2y + z = 10 2x – y + 3z = - 5 2x – 3y – 5z = 27 x + 2y + z = 10 -3[2x – y + 3z = - 5] 2[2x – y + 3z = - 5] 2x – 3y – 5z = 27 x + 2y + z = 10 -6x + 3y – 9z = 15 4x – 2y + 6z = -10 2x – 3y – 5z = 27 5x + 7z = 0 -4x – 14z = 42

15
3.5 – Solving Systems of Equations in Three Variables Ex. x + 2y + z = 10 2x – y + 3z = - 5 2x – 3y – 5z = 27 x + 2y + z = 10 -3[2x – y + 3z = - 5] 2[2x – y + 3z = - 5] 2x – 3y – 5z = 27 x + 2y + z = 10 -6x + 3y – 9z = 15 4x – 2y + 6z = -10 2x – 3y – 5z = 27 5x + 7z = 0 -4x – 14z = 42

16
3.5 – Solving Systems of Equations in Three Variables Ex. x + 2y + z = 10 2x – y + 3z = - 5 2x – 3y – 5z = 27 x + 2y + z = 10 -3[2x – y + 3z = - 5] 2[2x – y + 3z = - 5] 2x – 3y – 5z = 27 x + 2y + z = 10 -6x + 3y – 9z = 15 4x – 2y + 6z = -10 2x – 3y – 5z = 27 5x + 7z = 0 -4x – 14z = 42

17
3.5 – Solving Systems of Equations in Three Variables Ex. x + 2y + z = 10 2x – y + 3z = - 5 2x – 3y – 5z = 27 x + 2y + z = 10 -3[2x – y + 3z = - 5] 2[2x – y + 3z = - 5] 2x – 3y – 5z = 27 x + 2y + z = 10 -6x + 3y – 9z = 15 4x – 2y + 6z = -10 2x – 3y – 5z = 27 5x + 7z = 0 -4x – 14z = 42

18
5x + 7z = 0 -4x – 14z = 42

19
5x + 7z = 0 -4x – 14z = 42 2[5x + 7z = 0] -4x – 14z = 42

20
5x + 7z = 0 -4x – 14z = 42 2[5x + 7z = 0] -4x – 14z = 42 10x + 14z = 0 -4x – 14z = 42 6x = 42

21
5x + 7z = 0 -4x – 14z = 42 2[5x + 7z = 0] -4x – 14z = 42 10x + 14z = 0 -4x – 14z = 42 6x = 42

22
5x + 7z = 0 -4x – 14z = 42 2[5x + 7z = 0] -4x – 14z = 42 10x + 14z = 0 -4x – 14z = 42 6x = 42 x = 7

23
5x + 7z = 0 -4x – 14z = 42 2[5x + 7z = 0] -4x – 14z = 42 10x + 14z = 0 -4x – 14z = 42 6x = 42 x = 7 5x + 7z = 0

24
5x + 7z = 0 -4x – 14z = 42 2[5x + 7z = 0] -4x – 14z = 42 10x + 14z = 0 -4x – 14z = 42 6x = 42 x = 7 5x + 7z = 0 5(7) + 7z = 0

25
5x + 7z = 0 -4x – 14z = 42 2[5x + 7z = 0] -4x – 14z = 42 10x + 14z = 0 -4x – 14z = 42 6x = 42 x = 7 5x + 7z = 0 5(7) + 7z = 0 35 + 7z = 0

26
5x + 7z = 0 -4x – 14z = 42 2[5x + 7z = 0] -4x – 14z = 42 10x + 14z = 0 -4x – 14z = 42 6x = 42 x = 7 5x + 7z = 0 5(7) + 7z = 0 35 + 7z = 0 - 7z = -35

27
5x + 7z = 0 -4x – 14z = 42 2[5x + 7z = 0] -4x – 14z = 42 10x + 14z = 0 -4x – 14z = 42 6x = 42 x = 7 5x + 7z = 0 5(7) + 7z = 0 35 + 7z = 0 7z = -35 z = -5

28
5x + 7z = 0 -4x – 14z = 42 2[5x + 7z = 0] -4x – 14z = 42 10x + 14z = 0 -4x – 14z = 42 6x = 42 x = 7 5x + 7z = 0 5(7) + 7z = 0 35 + 7z = 0 7z = -35 z = -5

29
3.5 – Solving Systems of Equations in Three Variables Ex. x + 2y + z = 10 2x – y + 3z = - 5 2x – 3y – 5z = 27

30
3.5 – Solving Systems of Equations in Three Variables Ex. x + 2y + z = 10 2x – y + 3z = - 5 2x – 3y – 5z = 27

31
5x + 7z = 0 -4x – 14z = 42 2[5x + 7z = 0] -4x – 14z = 42 10x + 14z = 0 -4x – 14z = 42 6x = 42 x = 7 5x + 7z = 0 x + 2y + z = 10 5(7) + 7z = 0 35 + 7z = 0 7z = -35 z = -5

32
5x + 7z = 0 -4x – 14z = 42 2[5x + 7z = 0] -4x – 14z = 42 10x + 14z = 0 -4x – 14z = 42 6x = 42 x = 7 5x + 7z = 0 x + 2y + z = 10 5(7) + 7z = 0 7 + 2y – 5 = 10 35 + 7z = 0 7z = -35 z = -5

33
5x + 7z = 0 -4x – 14z = 42 2[5x + 7z = 0] -4x – 14z = 42 10x + 14z = 0 -4x – 14z = 42 6x = 42 x = 7 5x + 7z = 0 x + 2y + z = 10 5(7) + 7z = 0 7 + 2y – 5 = 10 35 + 7z = 0 2y + 2 = 10 7z = -35 z = -5

34
5x + 7z = 0 -4x – 14z = 42 2[5x + 7z = 0] -4x – 14z = 42 10x + 14z = 0 -4x – 14z = 42 6x = 42 x = 7 5x + 7z = 0 x + 2y + z = 10 5(7) + 7z = 0 7 + 2y – 5 = 10 35 + 7z = 0 2y + 2 = 10 7z = -35 2y = 8 z = -5

35
5x + 7z = 0 -4x – 14z = 42 2[5x + 7z = 0] -4x – 14z = 42 10x + 14z = 0 -4x – 14z = 42 6x = 42 x = 7 5x + 7z = 0 x + 2y + z = 10 5(7) + 7z = 0 7 + 2y – 5 = 10 35 + 7z = 0 2y + 2 = 10 7z = -35 2y = 8 z = -5 y = 4

36
5x + 7z = 0 -4x – 14z = 42 2[5x + 7z = 0] -4x – 14z = 42 10x + 14z = 0 -4x – 14z = 42 6x = 42 x = 7 5x + 7z = 0 x + 2y + z = 10 5(7) + 7z = 0 7 + 2y – 5 = 10 35 + 7z = 0 2y + 2 = 10 7z = -35 2y = 8 z = -5 y = 4

37
5x + 7z = 0 -4x – 14z = 42 2[5x + 7z = 0] -4x – 14z = 42 10x + 14z = 0 -4x – 14z = 42 6x = 42 x = 7 5x + 7z = 0 x + 2y + z = 10 5(7) + 7z = 0 7 + 2y – 5 = 10 35 + 7z = 0 2y + 2 = 10 7z = -35 2y = 8 z = -5 y = 4 (7,4,-5)

Similar presentations

© 2021 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google